Extending in vitro digestion models to specific human populations: Perspectives, practical tools and bio-relevant information. (February 2017) - Shani-Levi, Carmit; Alvito, Paula; Andrés, Ana; Assunção, Ricardo; Barberá, Reyes; Blanquet-Diot, Stéphanie; Bourlieu, Claire; Brodkorb, André; Cilla, Antonio; Deglaire, Amélie; Denis, Sylvain; Dupont, Didier; et al.
Abstract: Background: In vitro digestion models show great promise in facilitating the rationale design of foods. This paper provides a look into the current state of the art and outlines possible future paths for developments of digestion models recreating the diverse physiological conditions of specific groups of the human population. Scope and approach: Based on a collective effort of experts, this paper outlines considerations and parameters needed for development of new in vitro digestion models, e.g. gastric pH, enzymatic activities, gastric emptying rate and more. These and other parameters are detrimental to the adequate development of in vitro models that enable deeper insight into matters of food luminal breakdown as well as nutrient and nutraceutical bioaccessibility. Subsequently, we present an overview of some new and emerging in vitro digestion models mirroring the gastro-intestinal conditions of infants, the elderly and patients of cystic fibrosis or gastric bypass surgery. Key findings and conclusions: This paper calls for synchronization, harmonization and validation of potential developments in in vitro digestion models that would greatly facilitate manufacturing of foods tailored or even personalized, to a certain extent, to various strata of the human population. Highlights: In vitro digestion models show great promise in food and nutritional research. Paper outlines considerations for development of new in vitro digestion models. Human studies elucidate the variance of digestive conditions. Digestion models of infants, elderly and patients with GI disorders are reviewed.